DC Electric Field Meter for Project: Microstructural Changes in Snow During Equitemperature Metamorphism. - Dent, J. D. (1996)
A DC Electric Field Meter was purchased and assembled. This instrument will allow the measurement of the electric field produced near the earth's surface during blowing snow and blowing sand events. These measurements will in turn aid in the quantification of the effects of electrostatic forces on blowing snow and blowing sand particles; leading to better understanding and control of blowing snow and blowing sand and consequent drift formation.